2021
DOI: 10.3389/fmars.2021.750180
|View full text |Cite
|
Sign up to set email alerts
|

Pandora’s Box in the Deep Sea –Intraspecific Diversity Patterns and Distribution of Two Congeneric Scavenging Amphipods

Abstract: Paralicella tenuipesChevreux, 1908 and Paralicella caperescaShulenberger and Barnard, 1976 are known as widely distributed deep-sea scavenging amphipods. Some recent studies based on genetic data indicated the presence of high intraspecific variation of P. caperesca suggesting it is a species complex. Based on published molecular data from the Pacific and Indian oceans and new material obtained from the North and South Atlantic, we integrated the knowledge on the intraspecific variation and species distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Ritchie et al (2015) reported incongruence between the morphological and molecular identifications of two species within this genus but the discrepancies were not confirmed later (Mohrbeck et al, 2021). In contrast, high mean intraspecific divergences were reported for Paralicella caperesca (Jażdżewska et al, 2021;Mohrbeck et al, 2021). Our morphological study of the representatives of Paralicella separated them into two different groups, but they were further divided into molecular clades with non-distinct external appearance.…”
Section: Morphological Vs Molecular Identification Of Amphipodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Ritchie et al (2015) reported incongruence between the morphological and molecular identifications of two species within this genus but the discrepancies were not confirmed later (Mohrbeck et al, 2021). In contrast, high mean intraspecific divergences were reported for Paralicella caperesca (Jażdżewska et al, 2021;Mohrbeck et al, 2021). Our morphological study of the representatives of Paralicella separated them into two different groups, but they were further divided into molecular clades with non-distinct external appearance.…”
Section: Morphological Vs Molecular Identification Of Amphipodsmentioning
confidence: 70%
“…Some species from the superfamily Alicelloidea were collected as well. The genus Paralicella is known from all three oceans, including Antarctic waters (Chevreux, 1908;Shulenberger and Barnard, 1976;De Broyer et al, 2004; Horton and Thurston, 2009; Horton et al, 2020b;Weston et al, 2021;Jażdżewska et al, 2021) and has been collected at hydrothermal vent fields before (Barnard and Ingram, 1990), as has Valettiopsis (Juan de Fuca Ridge in the Pacific Ocean) (Tsurumi, 2001). The genus Parandania is not only a worldwide distributed genus, but was also sampled at hydrothermal vents (Wang et al, 2019).…”
Section: Scavenging Community In the Studied Areamentioning
confidence: 99%
“…While large spatial distributions are confirmed for some amphipod species (e.g., R . aculaeta , or scavenging Eurythenes gryllus and Paralicella tenuipes : Havermans et al, 2019 ; Jażdżewska et al, 2021 ; Lörz et al, 2018 ), these would have to be evaluated more precisely for H . propinqua (and most other species in the data set), so that with more corresponding data temperature optima for this species could shift.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also revealed that many undescribed deep-sea species are often much smaller than their shallow-water counterparts, a reason why these have been overlooked over the decades of deep-ocean exploration (Larsen, 2005;McCallum et al, 2015;Frutos et al, 2016). The number of new species and their enormous diversity discovered during each deep-sea expedition, confirms that oceanic bottom is the last recognized ecosystem of the Earth (Ramirez-Llodra et al, 2011;Frutos and Sorbe, 2014;Costello and Chaudhary, 2017;Jażdżewska et al, 2018Jażdżewska et al, , 2021. A paucity of specialists and awareness of the role taxonomy for understanding and protection of the biodiversity has meant that collections of invertebrates from deep-sea expeditions were shelved in museums awaiting the attention of taxonomists and formal description (Brandt et al, 2007;Appeltans et al, 2012).…”
Section: Introductionmentioning
confidence: 88%